2022
DOI: 10.3390/jpm12020310
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Detection in CT/X-ray Imagery Using Vision Transformers

Abstract: The steady spread of the 2019 Coronavirus disease has brought about human and economic losses, imposing a new lifestyle across the world. On this point, medical imaging tests such as computed tomography (CT) and X-ray have demonstrated a sound screening potential. Deep learning methodologies have evidenced superior image analysis capabilities with respect to prior handcrafted counterparts. In this paper, we propose a novel deep learning framework for Coronavirus detection using CT and X-ray images. In particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…In the event of an unbalanced small dataset, a modified version of the ResNet structure, that is, SCovNet, was used for testing. Performance metrics such as accuracy, specificity sensitivity, precision, F1-score and Matthews’s correlation coefficient are calculated using classifier-generated confusion matrix [42] , [43] , [44] , [45] , [46] . The accurately detected cases in the confusion matrix’s diagonal region are used to calculate the effectiveness of the deep learning classifier [44] , [45] .…”
Section: Resultsmentioning
confidence: 99%
“…In the event of an unbalanced small dataset, a modified version of the ResNet structure, that is, SCovNet, was used for testing. Performance metrics such as accuracy, specificity sensitivity, precision, F1-score and Matthews’s correlation coefficient are calculated using classifier-generated confusion matrix [42] , [43] , [44] , [45] , [46] . The accurately detected cases in the confusion matrix’s diagonal region are used to calculate the effectiveness of the deep learning classifier [44] , [45] .…”
Section: Resultsmentioning
confidence: 99%
“… where , , , and are the true positive, true negative, false positive, and false negative values, respectively. These evaluation metrics are used by several similar works in the literature [ 8 , 13 , 34 , 41 ]; thus, using them gives the ability to compare our results with those of the other studies and to be consistent with the assessment procedures of medical diagnostic systems [ 58 ]. These metrics are calculated from a confusion matrix.…”
Section: Resultsmentioning
confidence: 99%
“…The literature on COVID-19 reports several methods for the analysis of medical images such as of CT images [ 35 , 36 , 37 , 38 , 39 , 40 , 41 ], X-ray [ 42 , 43 , 44 , 45 , 46 , 47 ], and LUS [ 7 , 8 , 9 , 10 ]. For instance, Silva et al [ 35 ] proposed a voting-based approach, where the images from a given patient are classified using a group in a voting system.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed model is composed of three modules, which are a pretext channel module, a transformer-based transfer module, and a downstream channel module. Rahhal and colleagues [101] proposed a customized framework to classify X-ray and CT images [102,103]. The developed framework is symmetric and consists of two transformers.…”
Section: Classificationmentioning
confidence: 99%
“…The localization model UTRAD proposed by Chen et al [195], as shown in Table 3, is designed for both localization and detection using the same datasets [196,197,198]. The classification framework proposed by Rahhal and colleagues [101], as illustrated in Table 1, is also designed for image detection and the datasets used for model evaluation remain unchanged [102,103]. Captioning.…”
Section: Miscellaneousmentioning
confidence: 99%